2019
DOI: 10.1016/j.tet.2019.130726
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative synthesis of benzo[1,4]oxazines from α-branched primary amines and ortho-benzoquinones

Abstract: The efficient oxidative construction of benzo [1,4]oxazines from simple α-branched amines and ortho-benzoquinones is reported. The procedure pivots on a triethylamine and iodine mediated oxidative ring closure from the ketimine intermediate formed upon their condensation. This reaction was shown to tolerate a variety of α-branched benzylamines and downstream derivatization to substituted benzomorpholine structures was also demonstrated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This strategy was later extended by the same group to the synthesis of 1,4-benzoxazines. 68 Here, imine intermediates are converted into enamines under basic conditions, followed by the oxidation with iodine to provide -iodo imines. Finally, displacement of the iodide by the ortho-hydroxy group provides 1,4-benzoxazines.…”
Section: Review Synthesismentioning
confidence: 99%
“…This strategy was later extended by the same group to the synthesis of 1,4-benzoxazines. 68 Here, imine intermediates are converted into enamines under basic conditions, followed by the oxidation with iodine to provide -iodo imines. Finally, displacement of the iodide by the ortho-hydroxy group provides 1,4-benzoxazines.…”
Section: Review Synthesismentioning
confidence: 99%
“…The reactions of highly electrophilic and redox-active o-quinones with amines, which are vitally important in biomolecular chemistry as rational ways for selective biofunctionalization, 1 cross-linking transformations [2][3][4] and modeling enzymatic processes, 5,6 have been extensively employed for the syntheses of various five-membered, six-membered [7][8][9] and polycyclic 10,11 N,O-heterocyclic systems and o-aminophenols. 12 The detailed mechanisms and outcomes of these reactions, particularly those performed under oxidative conditions, are extremely sensitive to the structural peculiarities of the involved compounds and the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…12 The detailed mechanisms and outcomes of these reactions, particularly those performed under oxidative conditions, are extremely sensitive to the structural peculiarities of the involved compounds and the reaction conditions. 3,8,13 A representative example of the complexity of the mechanisms of quinone-amine reactions was given by the detailed study of the reaction between 4-methyl catechol ( precursor of the corresponding o-quinone) and propylamine performed under aerobic, oxidative and acidic conditions. 3 Using LC-MS techniques, it was found that more than 60 products, the majority of which were derived via the initial steps of 1,6-conjugate addition, Schiff base condensation and aroxyl phenol coup-ling, were formed within 6 min.…”
Section: Introductionmentioning
confidence: 99%
“…Reactivity of 3Hphenoxazin-3-ones is primarily determined by the properties of its p-quinone imine moiety. Therefore, these compounds can react with nucleophiles, in particular with amines, via one of the three pathways: Schiff base formation (attack at C(3) center), Michael type addition (at C(4)) or nucleophilic substitution (SNH) at C(2) center [13][14][15].…”
Section: Introductionmentioning
confidence: 99%